NEGATION AFFIXES IN ENGLISH - Dedy Subandowo (Premise: Journal of English Education and Applied Linguistics, 2014)
This research entitled "Negation Affixes in English". This study is aimed to describe the various negation affixes in English, morphological process, morphophonemic and meaning. The research data were taken from various sources of English grammar book, morphology, research journal and the book which relatees to the research. English grammar books used in this study are written by Otto Jesperson, Marcella Frank, Greenbaum and Geoffrey Leech.  The method used in this research is the descriptive-qualitative method. While the data collection techniques are performed by using jot-down method. And the results of analysis are presented in tabular form and descriptive method. The result of the research shows that English has six types of negative affixes which are categorized by the intensity of its appearance, such as dis-, in-, non-, un-, anti- and -less. Based on the function, negation affixes are divided into several categories such as adjectives, nouns, verbs, and adverbs. The morphophonemic affix in- has four allomorphs, they are in-, im-, il- and ir- . While the analysis revealed that negation affixes have some basic meanings, such as ‘not’, ‘without’, and ‘anti’.